KESEJAHTERAAN EMOSIONAL GURU PAUD: PENERAPAN TERAPI WARNA SUJOK DALAM MENINGKATKAN KUALITAS PENGAJARAN - Utomo, Agus Setyo; Hidayah, Nurul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The Emotional well-being plays a crucial role in enhancing teaching quality, particularly in Early Childhood Education (ECE), yet it is often overlooked. Sujok color therapy, which utilizes color psychology to balance emotions, emerges as an innovative approach to supporting teachers' emotional well-being. This study aims to analyze the implementation of Sujok color therapy among ECE teachers at TK Dharma Wanita Sumberporong Lawang as an effort to improve their emotional well-being. The method employed combines a mixed-method approach, incorporating both quantitative and qualitative techniques, with stages including hands-on education, counseling, and evaluation. The results indicate that the Sujok color therapy training effectively increased the teachers' knowledge and skills, with 50% of participants, initially categorized as having